Theachers opinions and communicative activities for eighth year students of basic educational Carlos Cueva Tamariz high school - Velecela Abambari, Silvia Geovanna
This study is concerned with the importance of oral skills in language learning at Carlos CuevaTamariz High School. A survey was applied to the English teachers of this high school to get to know their opinions about Our World Through English 1 (OWTE). The result showed that part of these teachers do not like the book because it does not provide enough time to 8th year students to speak. Also, many teachers think the topics of the book are not relevant or interesting for students. Based on these findings, a sample of communicative activities was provided at the end of this work. The first chapter deals with the description of the study, which describes the problem in 8thyears students atCarlos CuevaTamariz High Schoolface when learning English. Also this first part presents the aims of this research, and how they are going to be accomplished. Second part contains some insights about the relevant theoretical concepts. In fact, an overview of Communicative Language Teaching is presented as well as a brief description of the different types of communicative activities as a base of this research. Third part presents the summary of the major findings of this study which deal with teachers? opinions about speaking activities of OWTE. Based in these results, a group of communicative activities were designed in order to motivate students to speak.